The Comprehensive Systematic Review of What is The Relationship Between Pleural Effusion Characteristics and The Occurrence of Compressive Atelectasis in Adult Patients, as Evaluated Through Radiological Imaging Techniques? - Anisa Ayu Prasanti; Charles Sanjaya (International Medical Journal Corp. Ltd, 2026)
Introduction: Pleural effusions are a common clinical finding across diverse medical and surgical conditions, often leading to respiratory compromise. Compressive atelectasis, the collapse of lung tissue due to external pressure from pleural fluid, is a significant contributor to this morbidity. However, the precise relationship between specific characteristics of the effusion (e.g., volume, composition, laterality) and the occurrence of compressive atelectasis remains inadequately defined in adult populations (Chiumello et al., 2013; Muruganandan et al., 2020). Methods: A comprehensive systematic review was conducted, screening sources based on predefined criteria including adult population, presence of pleural effusion, assessment of effusion characteristics, evaluation of compressive atelectasis via radiological imaging, and appropriate study designs. Data were extracted from 80 heterogeneous sources, encompassing observational studies, randomized trials, and meta-analyses, focusing on population details, effusion characteristics, imaging methods, atelectasis definitions, and reported statistical relationships. Results: Direct evidence quantitatively linking effusion characteristics to compressive atelectasis was scarce. Larger effusion size (e.g., >500 mL) was associated with increased incidence of atelectasis, particularly in specific populations like lung transplant recipients (Krumm et al., 2024). Indirect evidence from drainage studies showed consistent improvements in oxygenation (PaO2/FiO2 ratio) and end-expiratory lung volume post-thoracentesis, especially in mechanically ventilated patients with hypoxemia (Goligher et al., 2011; Vetrugno et al., 2019; Chiu et al., 2024). Key thresholds emerged, suggesting drainage is most beneficial for effusions >400-500 mL or occupying ≥25% of the hemithorax, particularly when baseline P:F ratio is <200. The relationship is modulated by factors such as body position, underlying lung and pleural disease (e.g., trapped lung), and effusion etiology (Cortes-Puentes et al., 2018; Razazi et al., 2014). Discussion: The findings indicate that the development of compressive atelectasis is a multifactorial process, not solely dependent on effusion volume. Underlying pleural physiology (elastance), parenchymal compliance, patient positioning, and diaphragm function critically influence the outcome. Radiographic lung re-expansion post-drainage is a poor surrogate for physiological success, often discordant with pleural pressure measurements (Lester et al., 2022). The clinical implication is that management should be guided by physiology and symptoms, not just imaging appearance. Conclusion: While larger pleural effusions increase the risk of compressive atelectasis, the relationship is non-linear and significantly confounded by patient-specific factors. A standardized definition for compressive atelectasis and more studies directly correlating detailed effusion characteristics with radiologically defined atelectasis are needed. Clinically, drainage should be considered for symptomatic patients or mechanically ventilated patients with significant hypoxemia and effusions above volume thresholds, with an understanding that underlying lung condition dictates the response.